'We have the internet in our hands': Bangladeshi college students' use of ICTs for health information - Linda Waldman; Tanvir Ahmed; Nigel Scott; Shahinoor Akter; Hilary Standing; Sabrina Rasheed (BMC, 2018)
Abstract Background Information and Communications Technologies (ICTs) which enable people to access, use and promote health information through digital technology, promise important health systems innovations which can challenge gatekeepers' control of information, through processes of disintermediation. College students, in pursuit of sexual and reproductive health (SRH) information, are particularly affected by gatekeeping as strong social and cultural norms restrict their access to information and services. This paper examines mobile phone usage for obtaining health information in Mirzapur, Bangladesh. It contrasts college students' usage with that of the general population, asks whether students are using digital technologies for health information in innovative ways, and examines how gender affects this. Methods This study relies on two surveys: a 2013-2014 General Survey that randomly sampled 854 households drawn from the general population and a 2015 Student Survey that randomly sampled 436 students from two Mirzapur colleges. Select focus group discussions and in-depth interviews were undertaken with students. Icddr,b's Ethical Review Board granted ethical clearance. Results The data show that Mirzapur's college students are economically relatively well positioned, more likely to own mobile and smart phones, and more aware of the internet than the general population. They are interested in health information and use phones and computers to access information. Moreover, they use digital technology to share previously-discreet information, adding value to that information and bypassing former gatekeepers. But access to health information is not entirely unfettered, affecting male and female students differently, and powerful gatekeepers, both old and new, can still control sources of information. Conclusion Personal searches for SRH and the resultant online information shared through discrete, personal face-to-face discussions has some potential to challenge social norms. This is particularly so for women students, as sharing information may enable them to bypass gatekeepers and make decisions about reproduction. This suggests that digital health information seeking may be exercising a disruptive effect within the health sector. However, the extent of this disruption may depend, not on students' mobile phone usage, but on the degree to which powerful new gatekeepers are able to retain control over and market SRH information through students' peer-to-peer sharing.